Effects of anthropogenic infrastructures on the spatial ecology of raptors and bustards - Marques, Ana Teresa (2020)
Anthropogenic infrastructures are major drivers of human-related effects in the Anthropocene, and several important negative impacts on different taxa and habitats have been described. In the case of birds these impacts include, for example, habitat loss, mortality and changes in behaviour, which can have major consequences on the viability of populations. The main objective of this thesis was to study how anthropogenic infrastructures influence the distribution and movements of several bird species, in order to identify management actions and support conservation strategies. The thesis focuses on bustards and raptors species in the Iberian Peninsula, which are known to be vulnerable to human infrastructures such as roads, power lines and wind farms. Census data, mortality events in power lines and GPS tracking databases were used to study the interactions between infrastructures and the little bustard (Tetrax tetrax), great bustard (Otis tarda), black kite (Milvus migrans) and Iberian imperial eagle (Aquila adalberti). In general, this thesis shows that infrastructures, such as roads, power lines and wind turbines, can play an important role in species’ distribution (little bustard) and use of space (black kite and little bustard), and may even contribute to accentuate negative population trends (little bustard). Additionally, species features (e.g. morphology or behaviour) and ecology are essential to understand how they are affected and vulnerable to infrastructures. Guidelines for the management of infrastructures and conservation measures targeting vulnerable species are proposed.